Peningkatan Kadar Protein Putak melalui Fermentasi oleh Kapang Trichoderma reesei (THE INCREASE OF PROTEIN LEVEL FROM PUTAK THROUGH FERMENTATION OF FUNGI TRICHODERMA REESEI) - Hilakore, Maritje Aleonor; ., Suryahadi; Wiryawan, Komang; Mangunwijaya, Djumali (Jurnal Veteriner, 2013)
A study was conducted was to increasing the protein level in putak by fermentation using fungiTrichoderma reesei. A laboratoryum experimental study was conducted using  factorial CompletelyRandomized Design 3 x 4 x 3. The main factor is were  inoculant levels of fungi T. reesei (T): 5,0; 7,5 and 10,0% (w/w),the level  and the second factor were of incubation time (W):  2; 3; and 4 days. Variables tested werecrude protein (CP), true protein (TP) and crude fiber (CF). The result showed that  treatment with 7.5% ofT.reesei  and incubation time for 4 days gawe the highest of crude and true protein level (20,60%)  from14,17% and 13,25% from 3,25%, and  lowest crude fiber 9,08% from 9,70%. Through fermentation of  fungiT.reesei can be increase the protein and decrease the fiber level of putak.
Keywords: Corypha, gebang, putak, T. reesei